Studi Eksperimental Tekanan Ketaatan dan Personal Cost: Dampaknya terhadap Whistleblowing - Eka Widi Libriani; Intiyas Utami (Jurnal Akuntansi dan Bisnis, 2015)
Whistleblowing is a disclosure of fraud that is done by member of an organization on an illegal practice which happen in an organization. The obedience pressure from wrongdoer to the whistleblower can affect the whistleblower in making decision to report the fraud actions. The presence of personal cost which can be either a sanction or an act of revenge also can be considered by the whistleblower in doing the whistleblowing. This research aims to examine the effect of the obedience pressure and personal cost to the intention of doing whistleblowing. This research was conducted in Satya Wacana Christian University's with undergraduate accounting students from the Business and Economy Faculty as the participants. This study used an experimental design 2x2 between subject which consist of 105 bachelor degree of accounting students whose role as a accounting staff, generated 56 data ready to be analyzed. The results show that: 1) in a low condition of obedience pressure, the intention to do whistleblowing is higher than in high condition of obedience pressure; 2) in a low condition of personal cost, the intention to do whistleblowing is higher than in high condition of personal cost; 3) group who received lower obedience pressure and lower personal cost have the intention of the highest to do whistleblowing.